Cognitive deficits in older adults with mild cognitive impairment in a two-year follow-up study - Faria,Camila de Assis (2018)
ABSTRACT Characterizing cognitive decline in older adults with MCI over time is important to identify the cognitive profile of those who convert to dementia. Objective: This study examined the two-year cognitive trajectory of elderly adults diagnosed with MCI, from geriatrics and neurology outpatient clinics of a public hospital in Rio de Janeiro. Methods: 62 older adults with MCI were submitted to a neuropsychological battery and re-evaluated after two years. The Mann-Whitney U test was employed to assess differences between groups with respect to education, functioning, the Geriatric Depression Scale and diagnosis. Results: 24.2% converted to dementia after two years. The group with declines in two or more cognitive functions had a higher conversion rate to dementia than the group with decline in executive functions (EF) only (Z = -2.11, p = .04). The EF decline group had higher scores on the depression scale than both the memory decline group (Z = -1.99, p = .05) and multiple decline group (Z = -2.23, p = .03). Conclusion: The present study found different cognitive decline profiles in elderly adults with MCI and differences between them regarding depressive symptoms and rate of conversion to dementia.